Feasibility, acceptability and future adaptation of the Chinese translated Behavioural activation (C‐BA) treatment for depression: A pilot study. (24th July 2020) - Chen, Yun; Anand, Deepika; Li, Haolin; Xu, Peng; Daughters, Stacey B.
Abstract : Background: Although depression is prevalent among Chinese international students (CIS), only 4% of CIS seek treatment. Behavioural activation (BA) has been suggested as a culturally sensitive treatment for depression that has the potential to meet the clinical needs of CIS. The current pilot study tested the feasibility, acceptability and themes for future cultural adaptations of a Chinese translated BA treatment (C‐BA) among CIS. Methods: Six CIS with elevated depressive symptoms ( Beck Depression Inventory, BDI ≥ 14) completed a six‐session individual C‐BA treatment and assessments at pre‐ and post‐treatment and a 1‐month follow‐up. Primary outcome measures included treatment feasibility, acceptability and qualitative interview data informing future adaption of C‐BA. Exploratory analyses examined group changes in depressive symptoms over time and clinically significant symptom changes on individual levels. Results: All participants found the treatment to be highly feasible and culturally acceptable, and were highly engaged in the treatment. Themes of future cultural adaptions were generated from the qualitative interviews. Significant decreases in depressive symptoms were observed at a one1‐month post‐treatment follow‐up assessment. Conclusions: Preliminary evidence suggests that C‐BA has the potential to be a culturally sensitive treatment for depression among CIS. CIS demonstrated openness to psychotherapy and high treatment engagement.